IMPROVING STUDENTS’ WRITING SKILLS THROUGH SEMANTIC MAPPING TECHNIQUE IN GENRE-BASED APPROACH - Windi Isnandi Yanur; Nanik Supriani (Universitas Sarjanawiyata Tamansiswa, 2019)
The aims of this study are (1) to find out the problems of the students in writing, and (2) to find the effective ways of teaching applying semantic mapping technique in genre-based approach to improve writing skill for the tenth graders in SMK Nasional Berbah, Sleman. The study belongs to classroom action research. The object of this research was class X TP of SMK Nasional Berbah, Sleman. The researcher used semantic mapping technique that was combined with genre-based approach to resolve the students’ problem in writing. The researcher used qualitative analysis. The finding showed that (1) The problems in writing were (a) most of the students thought that writing was difficult task,(b) the students had difficulties to write a text, (c) the students still lacked of vocabulary, (d) the students had difficulties in developing ideas, (e) the students often made errors in grammatical rules when they wrote a text. (2) The effective ways of teaching applying semantic mapping technique in genre based approach consisted of four stages. (a) In BKOF, the researcher showed the picture about Parts of Motorcycle and drilled about specific words to the students. (b) in MOT, the researcher gave example of recount text and also some questions related to the topic. (c) in JCOT the researcher asked the students to make a list of main points and developed each point into some sentences. (d) in ICOT, the researcher asked the students to write a recount text individually based on their own ideas. The result of this study showed that semantic mapping technique could help the students to generate ideas, develop students’ ability in writing, and increase the students’ knowledege.